Kilka uwag o prawno-społecznym statusie kobiet w Chińskiej Republice Ludowej - Błaszczyk, Anna; Sikora, Michał (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article outlines the historical, cultural and legal background that shaped the position of women in the Middle Kingdom, and the protection of their rights and interests throughout the centuries. In traditionally patriarchal China, women have always assumed a subordinate position to men in the social hierarchy. For centuries, a woman’s role was limited by the domestic sphere and absolute submission to men, while a woman’s worth was determined solely by her ability to produce offspring, preferably male. A visible shift with regard to women’s role in Chinese society took place only in the twentieth century. The first pieces of legislation that comprehensively regulate the status of women were adopted in the People’s Republic of China, which officially declared gender equality practically from its very inception. In addition, the People’s Republic of China has also taken a number of measures to eradicate the traditional and significant disproportions between men and women visible in almost every area of social life that stemmed, to a large degree, from the influence of Confucianism. Despite the significant improvement in the situation of women – especially with regard to their legal protection – complete gender equality in practical terms has yet to be achieved in China
Keywords: Chiny; Chińska Republika Ludowa; konfucjanizm; prawo karne; prawo małżeńskie; konstytucja; równouprawnienie; prawa kobiet; krępowanie stóp